TiO2/ZnO/CuO/HDTMA-Br Composite for Photodegradation of Oxidative Compounds of Used Cooking Oil (UCO): Photodegradation of Free Fatty Acids and Peroxides - Adinda Pitaloka; Komar Sutriah; Sri Mulijani; Mohammad Khotib (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2026)
Used cooking oil (UCO) contains peroxide and FFA, which can impede UCO processing and lower the quality of downstream products. The majority of pretreatment techniques currently in use have drawbacks, such as excessive chemical use. An alternative that is more successful and efficient is photocatalysis. No research has been conducted on the photodegradation of UCO using TiO2/ZnO/CuO/HDTMA-Br composites. Precipitation was used to create the composite. The TiO2/ZnO/CuO composite has a high crystallinity, specifically 74.54% in the 1 CMC-modified catalyst, according to the characterization results. The spectrum of the synthesized TiO2/ZnO/CuO composite showed the presence of H2O and CO2 groups in addition to the primary groups of TiO2, ZnO, and CuO. Additionally, the 1 CMC modification increased pore volume and surface area. The surfactant-modified composite exhibited a more consistent morphology, as observed by SEM analysis. The best results from photocatalytic testing at different temperatures, times, and surfactant concentrations were obtained at 120 °C for an hour with a surfactant concentration of 1 CMC. These results show that degradation using TiO2/ZnO/CuO photocatalysts can lower the FFA and peroxide contents of UCO by 65% and 59%, respectively, under ideal conditions. This study focuses on FFA and peroxide value parameters as a preliminary investigation into alternative UCO pretreatment solutions. Copyright © 2026 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).